2017
DOI: 10.3389/fphar.2017.00158
|View full text |Cite
|
Sign up to set email alerts
|

An Introduction to Terminology and Methodology of Chemical Synergy—Perspectives from Across Disciplines

Abstract: The idea of synergistic interactions between drugs and chemicals has been an important issue in the biomedical world for over a century. As complex diseases, especially cancer, are being treated with various drug cocktails, understanding the interactions among these drugs is increasingly vital to ensuring successful treatment regimens. However, the idea of synergy is not limited to only the biomedical realm and these ideas have developed across many different disciplines, as well. In this review, we first disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
166
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(183 citation statements)
references
References 57 publications
(109 reference statements)
2
166
0
1
Order By: Relevance
“…where E c is the effect of the combination of two drugs (A and B) at given doses (a and b) [24]. The response to drug A at dose a is E a and E b indicates the effect of drug B at dose b. Deviation in observed effect greater than the expected effect determined from the reference model is considered a synergistic interaction; a negative deviation is considered an antagonistic combination.…”
Section: Cell Proliferation Assaysmentioning
confidence: 99%
“…where E c is the effect of the combination of two drugs (A and B) at given doses (a and b) [24]. The response to drug A at dose a is E a and E b indicates the effect of drug B at dose b. Deviation in observed effect greater than the expected effect determined from the reference model is considered a synergistic interaction; a negative deviation is considered an antagonistic combination.…”
Section: Cell Proliferation Assaysmentioning
confidence: 99%
“…Previous studies reported that combining osimertinib with an alternative RTK inhibitor may inhibit or treat the development of resistance driven by that specific RTK (7-9), whereas simultaneous inhibition of multiple parallel RTKs with osimertinib may be required to effectively potentiate osimertinib action (8). Further, while many studies show enhanced drug activity in combination therapies versus osimertinib treatment alone, they do not assess whether the effects of the 2-drug combinations are truly synergistic; synergistic interactions between therapeutics allow for maximization of the therapeutic effect while minimizing adverse events and may be required for effective therapeutic combinations with targeted agents (40). SOS1 is a common downstream mediator of RTK signaling.…”
Section: Sos1 Inhibition Synergizes With Egfr-tkis To Inhibit Cell Sumentioning
confidence: 99%
“…In the next, we put the multi-parametric optimization outputs into the context of existing synergistic concepts as conceived in the biomedical and farmacological studies of the simultaneous effects of therapeutic drugs (see e.g. [61,62]). Despite many alternative measures and approaches have been already proposed, the synergistic quantification of the optimization outputs is not straightforward.…”
Section: Synergistic Quantification Of Optimization Resultsmentioning
confidence: 99%